2021
DOI: 10.3390/app11073174
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered Activated Charcoal as a Medical Countermeasure for Acute Radiation Syndrome in Rats

Abstract: Activated charcoal (AC) can be taken orally as enterosorbent for treatment of pathological states related to exogenous and endogenous intoxications. Synthesized granulated AC with a highly developed active surface (SBET ~2700 m2/g) was used as a medical countermeasure (MCM) to acute radiation sickness (ARS) in rats after total body X-ray irradiation. AC demonstrates positive results in ARS treatment, as expressed in, (i) a decrease in body weight loss, (ii) a protection of bone marrow (BM) cells colony formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Microbiota restoration and protection, reduction of oxidative stress, protection and acceleration of bone barrow restoration, and recovery of plasmatic albumin structure and function by AC application are the facts, encouraging the application of AC for sepsis prevention [19,29,83,87,89,[150][151][152][153].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Microbiota restoration and protection, reduction of oxidative stress, protection and acceleration of bone barrow restoration, and recovery of plasmatic albumin structure and function by AC application are the facts, encouraging the application of AC for sepsis prevention [19,29,83,87,89,[150][151][152][153].…”
Section: Discussionmentioning
confidence: 97%
“…Enterosorption with highly activated AC with S BET 2200-2500 m 2 per/g helps to reduce oxidative stress and, possibly, by this way, accelerates the bone marrow restoration in experiments with rats after high-dose injections of the anti-cancer drug (melphalan), and after total body X-irradiation [150][151][152]. Monocyte LPS-induced ROS was attenuated with oral AC treatment in cirrhotic rats [103].…”
Section: Bone Marrow Index and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…AC-assisted protection of hematopoiesis has been also observed in the studies with IR-exposed laboratory animals in view of the possible mechanisms suggested above. This effect was significant regardless of how the animals were treated with AC: hemoperfusion [ 42 , 43 ] or enterosorption (p/o route) [ 43 , 44 ]. Supposedly, the effective myeloprotection with a subsequent BM recovery may influence survival rates of irradiated animals, according to the finding that a single-course low-volume hemoperfusion with uncoated spherical AC resulted in 60–70% increase in survival of dogs acutely irradiated with X-rays of the dose of 5.25 Gy, whereas survival without hemoperfusion was only 3% [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both ACs were obtained by the method of steam activation in the fluidized bed of the laboratory furnace. AC samples were evaluated using low-temperature nitrogen adsorption and the adsorption of albumin-bound toxins (unconjugated bilirubin) [1]. 45 Wistar female rats 2 months old were allocated into 3 groups: HSGD, CA-M, and Control.…”
mentioning
confidence: 99%